Pandemia sindémica em Portugal - Perelman, Julian (2022)
INTRODUCTION: International evidence has unveiled the existence of social inequalities in the risk of death associated with SARS-CoV-2 (COVID-19). In Portugal, the impossibility to identify the socioeconomic condition of deceased people hinders this evaluation. This study analyzes the social inequalities in the risk factors of COVID-19 mortality in Portugal. MATERIAL AND METHODS: We used data from the sixth National Health Survey, carried out between September 2019 and December 2019, for the subgroup of people aged between 25 and 79 years old (n = 12 052). We considered the comorbidities with demonstrated link to COVID-19 mortality: asthma, chronic bronchitis, cardiovascular (CVD) and cerebrovascular disease, diabetes, hypertension, chronic renal disease (CRD), and obesity. The inequality, stratified by sex, was measured in terms of education and income, using logistic regression (odds ratios and relative index of inequality). RESULTS: Compared to men with the lowest level of formal education, we measured a risk reduction, among men with tertiary education, of CVD (-90%), chronic bronchitis (-75%), stroke (-70%), diabetes (-62%), hypertension (-41%), and obesity (-43%). Among tertiaryeducated women, we observed a reduced risk of CRD (-77%), hypertension, diabetes, stroke (-70%), obesity (-64%), and CVD (-55%). Except for obesity among men, the risk of disease was always significantly lower in the highest income quintile, compared with the lowest. CONCLUSION: In 2019, we observed socioeconomic inequalities of high magnitude for the eight diseases with demonstrated link to COVID-19 mortality.